2015
DOI: 10.1080/17517575.2015.1019570
|View full text |Cite
|
Sign up to set email alerts
|

The intellectual core of enterprise information systems: a co-citation analysis

Abstract: Enterprise information systems (EISs) have evolved in the past 20 years, attracting the attention of international practitioners and scholars. Although literature reviews and analyses have been conducted to examine the multiple dimensions of EISs, no co-citation analysis has been conducted to examine the knowledge structures involved in EIS studies; thus, the current study fills this research gap. This study investigated the intellectual structures of EISs. All data source documents (1083 articles and 24,090 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 108 publications
(204 reference statements)
1
11
0
Order By: Relevance
“…An Enterprise Resource Planning (ERP) system helps organizations to support and integrate business functions and ensure their operations are appropriately set, which, in turn, help them to achieve long-term growth and sustainability [1]. Successful implementation is an essential factor when studying the intellectual structure of ERP systems [2]. Shiau (2016) [2] performed a co-citation analysis of thousands of articles to examine the knowledge structures involved in ERP studies, and concluded that the implementation of an ERP is challenging, and each organization exhibits specific considerations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An Enterprise Resource Planning (ERP) system helps organizations to support and integrate business functions and ensure their operations are appropriately set, which, in turn, help them to achieve long-term growth and sustainability [1]. Successful implementation is an essential factor when studying the intellectual structure of ERP systems [2]. Shiau (2016) [2] performed a co-citation analysis of thousands of articles to examine the knowledge structures involved in ERP studies, and concluded that the implementation of an ERP is challenging, and each organization exhibits specific considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Successful implementation is an essential factor when studying the intellectual structure of ERP systems [2]. Shiau (2016) [2] performed a co-citation analysis of thousands of articles to examine the knowledge structures involved in ERP studies, and concluded that the implementation of an ERP is challenging, and each organization exhibits specific considerations. Thus, the study of acceptance and success of information technology in organizations is an important subject to be studied in order to obtain sustainability and competitive advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Citation and co-citation analyses are commonly used bibliometric methods for assessing consistent study areas among fields (Small 1973;Sugimoto et al 2008;Shiau and Dwivedi 2013;Shiau 2015;Shiau et al 2015). Moreover, cluster analysis and multidimensional scaling (MDS) analysis were performed to identify the core knowledge of the social networking.…”
Section: Introductionmentioning
confidence: 99%
“…Factors affecting the implementation and success of information systems (IS) attract the attention of practitioners and scholars (Shiau, 2016). Literature analysis shows that there are two flows in research papers.…”
Section: Introductionmentioning
confidence: 99%